Production of the Co-pelletizing Fuel from Domestic Wastewater Sludge and Non-recyclable Waste - Chiraniramai , Kosin; Chooaksorn, Wanida (Burapha Science Journal, 2024)
Background and Objectives : Non-recyclable waste (N-RW) cannot be efficiently disposed of while sludge from domestic wastewater treatment (DWS) must be disposed of by landfill. Decomposition in the landfill site causes greenhouse gases. Non-recyclable waste can be burned to produce energy with a binder for forming. The objective of this research is to study the characteristics of co-pelletizing fuel from non-recyclable waste which DWS was used as binders. Methodology : The moisture content, mixing ratio, and ignition ability of co-pelletizing fuels were conducted. The study was done at a moisture content of 0%, 20%, and 30% according to the ratio of DWS : N-RW including of 8:2, 7:3, 5:5, 3:7, and 2:8 respectively. The physical and chemical properties were analyzed including bulk density, moisture content, ash content, volatile matter, fixed carbon, and heat value according to the standards of the American Society for Testing and Materials (ASTM). Main Results : The co-fuel can be pelletized at the moisture content of 20% and ratios of DWS : N-RW of 5:5, 3:7, and 2:8. The co-pelletizing fuel was suitable according to standards, guidelines, and waste qualification criteria for processing into fuel briquette and the interlocking block of the Department of Industrial Works. The ash content was 19.10+0.44%, 16.07+0.21%, and 14.92+0.34%, respectively. The heat value increased as the proportion of sludge from domestic wastewater sludge decreased, 4,518+159, 6,781+42, and 7,532+346 kcal/kg, respectively. For ignition, co-pelletizing fuel at a ratio of 2:8 could ignite for the longest time of 205+5.3 seconds. Conclusions : The Moisture content is 20%, and co-fuel can be pelletized at a ratios of DWS : N-RW of 2:8 which is most appropriate. The co-pelletizing fuel has a heat value of 7,532+346 kcal/kg, ash content of 14.92+0.34%, and ignite time of 205 +5.3 seconds.